2020
DOI: 10.3390/biomedicines8090305
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of Bilayer Scaffolds Electrospun from Chitosan/Alginate-Chitin Nanowhiskers

Abstract: In this work, a bilayer chitosan/sodium alginate scaffold was prepared via a needleless electrospinning technique. The layer of sodium alginate was electrospun over the layer of chitosan. The introduction of partially deacetylated chitin nanowhiskers (CNW) stabilized the electrospinning and increased the spinnability of the sodium alginate solution. A CNW concentration of 7.5% provided optimal solution viscosity and structurization due to electrostatic interactions and the formation of a polyelectrolyte comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…This study was performed using crab shell chitosan (Bioprogress, Shchelkovo, Russia) with a viscosity average molecular weight (M η ) of 1.6 × 10 5 and a degree of deacetylation of 0.80 [9], sodium hyaluronate (Shandong Focuchem Biotech Co., Qufu, Shandong, China) with M η of 5.4 × 10 4 [27], sodium alginate (Qingdao Bright Moon Seaweed Group Co. Ltd., Qingdao, Shandong, China) with M η of 1.3 × 10 5 [28], and sodium sulfoethyl cellulose with M η of 1.4 × 10 4 and a degree of substitution of 0.80 (the sample was prepared and characterized according to [4]).…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed using crab shell chitosan (Bioprogress, Shchelkovo, Russia) with a viscosity average molecular weight (M η ) of 1.6 × 10 5 and a degree of deacetylation of 0.80 [9], sodium hyaluronate (Shandong Focuchem Biotech Co., Qufu, Shandong, China) with M η of 5.4 × 10 4 [27], sodium alginate (Qingdao Bright Moon Seaweed Group Co. Ltd., Qingdao, Shandong, China) with M η of 1.3 × 10 5 [28], and sodium sulfoethyl cellulose with M η of 1.4 × 10 4 and a degree of substitution of 0.80 (the sample was prepared and characterized according to [4]).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a bilayer scaffold consisting of chitosan and alginate-chitin nano-whiskers electrospun NFs was found to promote mesenchymal stem cell proliferation at the same time ensuring antibacterial properties. [250] Yet, a multilayered nanofibrous scaffold consisting of a sandwich-like structure comprised of two hydrophobic PCL nanofibrous layers and a hydrophilic alginate-based one was investigated for bone tissue regeneration. [251] The effect of multilayer deposition of NFs was observed in terms of an increase in the water absorption, a slower degradation rate, and improved mechanical properties together with marked ability to foster cell viability.…”
Section: Tissue Engineering and Wound Healingmentioning
confidence: 99%
“…These scaffolds exhibit increased mouse calvarial preosteoblast adhesion and proliferation compared to those made of alginate alone due to the presence of chitosan, which promotes the adsorption of serum proteins, while alginate is naturally nonadhesive to cells. Petrova et al [87,88] showed that the addition of the second electrospun layer of polyanion (hyaluronic acid or sodium alginate) on the freshly electrospun chitosan nanofibers induced the polyelectrolyte interaction that resulted in insoluble matrices with enhanced mechanical properties and good cytocompatibility with mesenchymal stem cells. Polysaccharide electrospun scaffolds have been intensively used to determine in vivo effects on calvaria bone defect models.…”
Section: Tissue Engineeringmentioning
confidence: 99%